2011
DOI: 10.3749/canmin.49.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Dissymmetrization in tourmaline: the atomic arrangement of sectorally zoned triclinic Ni-bearing dravite

Abstract: Although putatively possessing hexagonal R3m symmetry, reports of optically anomalous tourmaline are common, and recently an occurrence of triclinic tourmaline was reported with dissymmetrization that resulted from non-equivalency of the occupants of the Y sites. We report the atomic arrangement of Ni-bearing dravite from the Berezovskoe gold deposit, Middle Urals, Russia, in the non-conventional triclinic space-group R1 (R = 4.41%) to facilitate comparison with the conventional tourmaline R3m cell. The dissym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
(28 reference statements)
1
12
0
Order By: Relevance
“…The possible biaxial subsymmetries of space group R3m are the subgroups Cm (monoclinic) and P1 (triclinic). Thus, in accord with the studies of [12][13][14], we selected the space-group type P1 for the refinement in line with the significant departure of α and β from 90 • in unconstrained unit-cell refinements. To facilitate the comparison between triclinic and trigonal structures, the primitive triclinic cell used in this study [e.g., sample LUI-AUS, a = 7.20820 (10), b = 9.5000(2), c = 9.4947(2) Å, α = 113.7519(8) • , β = 104.5539(8) • , γ = 104.6823 (9) • and V = 527.835(18) Å 3 ] was recast in the non-standard space-group R1, defining a pseudohexagonal unit-cell similar to the typical hexagonal triple R cell but with unconstrained unit-cell parameters (Table 3).…”
Section: Crystal Structurementioning
confidence: 99%
“…The possible biaxial subsymmetries of space group R3m are the subgroups Cm (monoclinic) and P1 (triclinic). Thus, in accord with the studies of [12][13][14], we selected the space-group type P1 for the refinement in line with the significant departure of α and β from 90 • in unconstrained unit-cell refinements. To facilitate the comparison between triclinic and trigonal structures, the primitive triclinic cell used in this study [e.g., sample LUI-AUS, a = 7.20820 (10), b = 9.5000(2), c = 9.4947(2) Å, α = 113.7519(8) • , β = 104.5539(8) • , γ = 104.6823 (9) • and V = 527.835(18) Å 3 ] was recast in the non-standard space-group R1, defining a pseudohexagonal unit-cell similar to the typical hexagonal triple R cell but with unconstrained unit-cell parameters (Table 3).…”
Section: Crystal Structurementioning
confidence: 99%
“…General criteria that regulate the patterns of distribution of transitionmetal cations over octahedrally coordinated positions are at present unavailable. Most authors agree that large divalent transition-metal cations (Mn 2+ , Fe 2+ , Cu 2+ , Co 2+ , Ni 2+ ) position themselves solely or predominantly in the Y octahedron (Burns et al, 1994;Bloodaxe et al, 1999;MacDonald and Hawthorne, 1995a;Hughes et al, 2011). Regularities of these cation occurrences in the Z octahedron are the subject of scientific debate.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports of Ni 2+ in natural tourmalines (Henry and Dutrow, 2001;Baksheev and Kudryavtseva, 2004;Hughes et al, 2011); the Ni content does not exceed 4 wt.% of NiO (Baksheev and Kudryavtseva, 2004). In these areas we have attempted to study crystal-chemical regularities of Ni-bearing tourmalines using synthetic crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The mineralogical study confirmed the first identification, pointing out a high Ni content and suggesting the necessity of its full crystal-chemical investigation. Indeed, nickeloan tourmalines have been reported from a few localities worldwide (e.g., Henry and Dutrow 2001;Baksheev and Kudryavtseva 2004;Voudouris et al 2019) and structural data have been mainly collected on synthetic analogs (e.g., Rozhdestvenskaya et al 2012;Vereshchagin et al 2015); the only natural refined sample was reported as triclinic (Hughes et al 2011).…”
Section: Introductionmentioning
confidence: 99%